Genotype-environment interaction and stability analysis of four fine rice varieties (Journal of the Bangladesh Agricultural University, 2012)
Genotype-environment interactions through different stability parameters and performance traits of four fine rice genotypes were studied. The traits were; days to 50% flowering, days to maturity, plant height (cm), number of effective tillers per hill, panicle length (cm), number of fertile grains per panicle, number of sterile grains per panicle and yield (t/ha) in four fine rice genotypes across nine environments along with experimental farm of Genetics and Plant Breeding department, Bangladesh Agricultural University (BAU) Mymensingh. Significant differences were observed for genotypes, environments and genotypesenvironment interaction. Stability analysis after Eberhat and Russells model suggested that the genotypes used in study were more or less responsive to environmental changes. Most of the genotypes performed better in Comilla. BAU125 was found stable for effective tillers per hill and comparatively less sensitive to other genotypes in panicle length and number of sterile grains per panicle. BR5 was stable for days to maturity and plant height whereas Kalizira performed better than other genotypes for fertile grains per panicle. In general, only the genotype BAU125 was found stable for effective tillers per hill, panicle length and lowest number of sterile grains per panicle.   DOI: http://dx.doi.org/10.3329/jbau.v10i1.12011   J. Bangladesh Agril. Univ. 10(1): 17, 2012